Diet knowledge, Self Efficacy and Motivation for Hypertension Prevention Behavior - Donny Tri Wahyudi (Alta Dharma Publisher, 2020)
Background: Preventive behavior requires an individual's desire and ability to be able to control blood pressure. The purpose of this research is to analyze dietary knowledge, self-efficacy and motivation towards hypertension prevention behavior in the elderly. Methods: Analytical research with cross sectional approach. Results: C-Square statistical test showed diet knowledge, motivation towards hypertension prevention behavior p = <? = 0.05. While self-efficacy of hypertension prevention behavior p => ? = 0.05. Conclusion: Knowledge of diet, motivation influences hypertension prevention behavior whereas self efficacy does not affect hypertension prevention behavior. Recommendation: It is expected to conduct further research related to the effect of social support and effective methods of providing information in increasing self-efficacy